Innate/Inflammatory Bioregulation of Surfactant Protein D Alleviates Rat Osteoarthritis by Inhibiting Toll-Like Receptor 4 Signaling - Jiang, Huanyu; Zhang, Yubiao; Hu, Geliang; Shang, Xiaobin; Ming, Jianghua; Deng, Ming; Li, Yaming; Ma, Yonggang; Liu, Shiqing; Zhou, Yan (Frontiers in Immunology, 2022)
Osteoarthritis (OA) is a deteriorating disease of cartilage tissues mainly characterized as low-grade inflammation of the joint. Innate immune molecule surfactant protein D (SP-D) is a member of collectin family of collagenous Ca2+-dependent defense lectins and plays a vital role in the inflammatory and innate immune responses. The present study investigated the SP-D-mediated innate/inflammatory bioregulation in OA and explored the underlying molecular mechanism. Transcriptome analysis revealed that SP-D regulated genes were strongly enriched in the inflammatory response, immune response, cellular response to lipopolysaccharide (LPS), PI3K-Akt signaling, Toll-like receptor (TLR) signaling, and extracellular matrix (ECM)-receptor interaction pathways. Knockdown of the SP-D gene by the recombinant adeno-associated virus promoted the macrophage specific markers of CD68, F4/80 and TLR4 in the articular cartilage in vivo. SP-D alleviated the infiltration of synovial macrophages and neutrophils, and inhibited TLR4, TNF-α and the phosphorylation of PI3K, Akt and NF-κB p65 in cartilage. SP-D suppressed cartilage degeneration, inflammatory and immune responses in the rat OA model, whilst TAK-242 strengthened this improvement. In in vitro conditions, SP-D pre-treatment inhibited LPS-induced overproduction of inflammation-correlated cytokines such as IL-1β and TNF-α, and suppressed the overexpression of TLR4, MD-2 and NLRP3. SP-D prevented the LPS-induced degradation of ECM by down-regulating MMP-13 and up-regulating collagen II. Blocking of TLR4 by TAK-242 further enhanced these manifestations. We also demonstrated that SP-D binds to the TLR4/MD-2 complex to suppress TLR4-mediated PI3K/Akt and NF-κB signaling activation in chondrocytes. Taken together, these findings indicate that SP-D has chondroprotective properties dependent on TLR4-mediated PI3K/Akt and NF-κB signaling and that SP-D has an optimal bioregulatory effect on the inflammatory and innate responses in OA.